1998
DOI: 10.1034/j.1399-0004.1998.531530113.x
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 deletions in a series of patients with non-selective congenital heart defects: incidence, type of defects and parental origin

Abstract: Previous studies have indicated a wide spectrum of incidences of 22q11.2 deletions in isolated and syndromic (sporadic or familial) cases of conotruncal heart defects, whereby the detection rate of the deletion varied from 65% in one study to 0 in another. We analysed 110 patients with non-selective syndromic or isolated non-familial congenital heart malformations by fluorescence in situ hybridization (FISH) using the D22S75 DiGeorge chromosome (DGS) region probe. A 22q11.2 microdeletion has been detected in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…Our results confirm the observations brought back by some authors concluding that congenital heart disorders isolated are hardly the consequence of microdeletion 22q11.2 [6,12,28,29] or of microdeletion 10p13-14 [30].…”
Section: Exclusion Of Chromosomal Abnormalities and Microdeletions 22supporting
confidence: 82%
See 1 more Smart Citation
“…Our results confirm the observations brought back by some authors concluding that congenital heart disorders isolated are hardly the consequence of microdeletion 22q11.2 [6,12,28,29] or of microdeletion 10p13-14 [30].…”
Section: Exclusion Of Chromosomal Abnormalities and Microdeletions 22supporting
confidence: 82%
“…Microdeletions of chromosomal region 22q11.2 are actually more considered as a principal cause of Di George syndrome [7,8], velocardiofacial syndrome [9] and conotruncal anomaly face syndrome [10,11]. The haploinsufficiency of 22q11 has been found also in some familial cases of heart disease [8,12] and in sporadic patients with isolated CHD [13][14][15][16][17].…”
mentioning
confidence: 99%
“…There are several studies on the prevalence of individual chromosomal abnormalities, like 22q11.2 deletions [31][32][33] (velocardiofacial and DiGeorge syndromes are due to 22q11.2 deletions). Borgmann et al 31 found that routine screening for 22q11.2 deletions in nonsyndromic CHD subjects gave no yield.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in genetic science has disclosed new etiologies for CHD, e.g. microdeletion syndromes [17]. Detection of a CHD should be followed by a thorough clinical and laboratory examination for associated malformations and genetic disorders.…”
Section: Associated Syndromes/malformationsmentioning
confidence: 99%